Phenolic Compounds Affect Bloat Potential of Wheat Forage. Issue 1 (11th December 2015) - Malinowski, Dariusz P.; Pinchak, William E.; Min, Byeng R.; Rudd, Jackie C.; Baker, Jason
Abstract : Winter wheat ( Triticum aestivum L.) is the major source of high‐quality winter forage for grazing cattle ( Bos taurus L.) in the southern Great Plains of the United States. High concentrations of crude protein and soluble nitrogen fractions in wheat forage are often associated with frothy bloat conditions in cattle. The death loss of stocker cattle grazing wheat due to bloat ranges 2 to 3% in the southern Great Plains each year. The occurrence of frothy bloat in cattle grazing on wheat forage is affected by a number of factors, including complex relationships among wheat plant metabolism, cattle genetics, environmental conditions, and ruminal microbial activity. Traditional approaches to control frothy bloat rely on feed supplements such as surfactants and ionophores, grass hay, and condensed tannins. In a series of experiments conducted at Vernon and Chillicothe, TX, during 2004 to 2006, we determined correlations between total phenolic concentrations in wheat forage and foam strength (an estimate of the bloat potential) in a range of wheat breeding lines and commercial cultivars evaluated by the Wheat Breeding Program of Texas A&M AgriLife Research. Total phenolic concentration was inversely correlated with foam strength in each growing season. Wheat cultivars and experimental breeding lines differed in total phenolic concentration in forage, suggesting a potential for development of cultivars with higher phenolic content in forage as a measure to decrease bloat occurrences in grazing cattle.